El enfoque meta-analítico de generalización de la fiabilidad - López-Pina, Jose Antonio (2012)
Sentences such as «the test reliability is 0.80» are wrong. It is more appropriate to say «the test scores reliability in a given application of it is 0.80». The meta-analytic approach of reliability generalization pretends to show that reliability is an empirical property that varies from one test application to another. This recent meta-analytic approach is helping to make the researchers aware of the importance of reporting reliability estimates obtained from the own data and, of avoiding the malpractice of inducting reliability coefficients from other studies and previous applications of the test. The stages to carry out a reliability generalization study are presented: (a) formulating the problem, (b) searching for the studies, (c) coding studies, (d) statistical analysis and interpretation, and (e) publication. An updated overview of the statistical problems of this approach: (a) to transform versus not to transform the reliability coefficients, (b) to weight versus not to weight the coefficients, (c) how to manage statistical dependency among the coefficients, and (d) which statistical model is the most appropriate (fixed-, random-, and mixed-effects).ResumenFrases del tipo «la fiabilidad del test es 0.80» son incorrectas. Es más apropiado decir «la fiabilidad de las puntuaciones del test en una determinada aplicación del mismo es 0.80». El enfoque meta-analítico de generalización de la fiabilidad pretende demostrar que la fiabilidad es una propiedad empírica que varía de una aplicación a otra del test. Este nuevo enfoque meta-analítico está contribuyendo a concienciar a los investigadores sobre la importancia de aportar estimaciones de la fiabilidad con los propios datos y evitar inducciones de la fiabilidad. Se presentan las fases en las que se lleva a cabo un estudio de generalización de la fiabilidad: (a) formulación del problema, (b) búsqueda de los estudios, (c) codificación de los estudios, (d) análisis estadístico e interpretación y (e) publicación. Se presenta una visión actualizada de los problemas estadísticos de este enfoque: (a) transformar versus no transformar los coeficientes, (b) ponderar versus no ponderar los coeficientes, (c) cómo tratar la dependencia estadística entre los coeficientes y (d) cuál es el modelo estadístico más apropiado (efectos fijos, efectos aleatorios, efectos mixtos).AbstractSentences such as «the test reliability is 0.80» are wrong. It is more appropriate to say «the test scores reliability in a given application of it is 0.80». The meta-analytic approach of reliability generalization pretends to show that reliability is an empirical property that varies from one test application to another. This recent meta-analytic approach is helping to make the researchers aware of the importance of reporting reliability estimates obtained from the own data and, of avoiding the malpractice of inducting reliability coefficients from other studies and previous applications of the test. The stages to carry out a reliability generalization study are presented: (a) formulating the problem, (b) searching for the studies, (c) coding studies, (d) statistical analysis and interpretation, and (e) publication. An updated overview of the statistical problems of this approach: (a) to transform versus not to transform the reliability coefficients, (b) to weight versus not to weight the coefficients, (c) how to manage statistical dependency among the coefficients, and (d) which statistical model is the most appropriate (fixed-, random-, and mixed-effects)